Magnetic Resonance Imaging and X-Ray Imaging Properties of Ultrasmall Lanthanide Oxide (Ln = Eu, Gd, and Tb) Nanoparticles Synthesized via Thermal Decomposition - Shuwen Liu; Tirusew Tegafaw; Son Long Ho; Huan Yue; Dejun Zhao; Ying Liu; Endale Mulugeta; Xiaoran Chen; Hansol Lee; Dabin Ahn; Ji-ung Yang; Ji Ae Park; et al. (Molecules, 2025)
Owing to their 4f electrons and high atomic numbers, lanthanide (Ln) elements impart lanthanide oxide (Ln2O3) nanoparticles with excellent biomedical imaging properties. This study reports synthesis for three types of ultrasmall and monodisperse Ln2O3 nanoparticles (Ln = Eu, Gd, and Tb) via thermal decomposition in oleylamine at 280 °C, followed by ligand exchange with citric acid (CA) to produce water-dispersible, CA-grafted Ln2O3 nanoparticles with high colloidal stability. The resulting CA-grafted Ln2O3 nanoparticles had average diameters of approximately 2 nm. We characterized their physicochemical properties, including in vitro cytotoxicity, magnetic resonance imaging properties (i.e., water proton spin relaxivities), and X-ray imaging properties (i.e., X-ray attenuation).